1998
DOI: 10.1051/aas:1998271
|View full text |Cite
|
Sign up to set email alerts
|

Catalogue of HII regions measured on 6 m telescope plates at Observatoire de Marseille

Abstract: Abstract. Several galaxies were studied at Observatoire de Marseille using the films obtained at the 6 m telescope with the Great Focal Reducer installed at the prime focus of the russian telescope.We thought that before we retire, it should be of some interest for the astronomical community to find in a single catalogue all the data we published to facilitate the research. (see hereunder the references).We give in this catalogue the data of the following galaxies: M 33, M 51, M 81, NGC 2403, NGC 4258 and NGC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The characteristics of HII regions have been studied in many extragalactic Hα surveys [e.g. Knapen (1998) and references therein; Petit et al (1998); Thilker et al (2002); Kennicutt et al (2008)]. The studies by Kennicutt (1988) and Kennicutt et al (1989, KEH89 hereafter) of the population of HII regions in nearby galaxies confirmed that HII region population properties are strongly dependent on the host galaxy Hubble type.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of HII regions have been studied in many extragalactic Hα surveys [e.g. Knapen (1998) and references therein; Petit et al (1998); Thilker et al (2002); Kennicutt et al (2008)]. The studies by Kennicutt (1988) and Kennicutt et al (1989, KEH89 hereafter) of the population of HII regions in nearby galaxies confirmed that HII region population properties are strongly dependent on the host galaxy Hubble type.…”
Section: Introductionmentioning
confidence: 99%
“…At least 50 of them are in binary and multiple systems, and it is still difficult to tell which of the remaining 43 is isolated. Of the 491 variable stars closer than 22 pc from the sun, 111 are UV Ceti flare stars, of which 55 are members of binary or multiple systems [8]. Thus, it is natural to assume that membership in a binary of multiple system is a characteristic feature of flare stars in the sun's neighborhood and may play an important role in the active physical processes observed in these stars.…”
Section: Introductionmentioning
confidence: 99%
“…His light curve was rather erratic and undersampled and has never been verified so that we believe that it was spurious. Unfortunately, it made its way through the literature and was cited in the catalogs by Kukarkin et al (1982), Petit (1990), and Strassmeier et al (1993). The most recent photometry that we are aware of is that by Krisciunas & Guinan (1990), who observed the star independently between 1981 and 1990.…”
Section: Introductionmentioning
confidence: 99%